Perioperative Aspirin Use Is Associated with Bleeding Complications during Robotic Partial Nephrectomy. Issue 2 (23rd February 2022) - Delto, Joan C.; Fleishman, Aaron; Chang, Peter; Jiang, Da David; Hyde, Sara; McAnally, Kyle; Crociani, Catrina; Jamil, Marcus; Patel, Hiten D.; Pavlinec, Jonathan; Budzyn, Jeffrey; Durant, Adri; et al.
Abstract : Purpose: Daily aspirin use following cardiovascular intervention is commonplace and creates concern regarding bleeding risk in patients undergoing surgery. Despite its cardio-protective role, aspirin is often discontinued 5–7 days prior to major surgery due to bleeding concerns. Single institution studies have investigated perioperative outcomes of aspirin use in robotic partial nephrectomy (RPN). We sought to evaluate the outcomes of perioperative aspirin (pASA) use during RPN in a multicenter setting. Materials and Methods: We performed a retrospective evaluation of patients undergoing RPN at 5 high volume RPN institutions. We compared perioperative outcomes of patients taking pASA (81 mg) to those not on aspirin. We analyzed the association between pASA use and perioperative transfusion. Results: Of 1, 565 patients undergoing RPN, 228 (14.5%) patients continued pASA and were older (62.8 vs 56.8 years, p <0.001) with higher Charlson scores (mean 3 vs 2, p <0.001). pASA was associated with increased perioperative blood transfusions (11% vs 4%, p <0.001) and major complications (10% vs 3%, p <0.001). On multivariable analysis, pASA was associated with increased transfusion risk (OR 1.94, 1.10–3.45, 95% CI). Conclusions: In experienced hands, perioperative aspirin 81 mg use during RPN is reasonable and safe; however, there is a higher risk of blood transfusions and major complications. Future studies are needed to clarify the role of antiplatelet therapy in RPN patients requiring pASA for primary or secondary prevention of cardiovascular events.